algebra

posted by .

Did I do this problem the correct way if so is there a shorter way to explain this?
x(x + 6)(x + -4) = 24x
x(6 + x)(x + -4) = 24x
x(6 + x)(-4 + x) = 24x
(6 + x) * (-4 + x
x(6(-4 + x) + x(-4 + x)) = 24x
x((-4 * 6 + x * 6) + x(-4 + x)) = 24x
x((-24 + 6x) + x(-4 + x)) = 24x
x(-24 + 6x + (-4 * x + x * x)) = 24x
x(-24 + 6x + (-4x + x2)) = 24x
6x + -4x = 2x
x(-24 + 2x + x2) = 24x
(-24 * x + 2x * x + x2 * x) = 24x
(-24x + 2x2 + x3) = 24x
-24x + 2x2 + x3 = 24x
-24x + -24x + 2x2 + x3 = 24x + -24x
-24x + -24x = -48x
-48x + 2x2 + x3 = 24x + -24x
24x + -24x = 0
-48x + 2x2 + x3 = 0
x(-48 + 2x + x2) = 0
x((-8 + -1x)(6 + -1x)) = 0
x = 0
-8 + 8 + -1x = 0 + 8
0 + -1x = 0 + 8
-1x = 0 + 8
-1x = 8
x = -8
x = {0, -8, 6}

  • algebra -

    First of all, x=0 is clearly a solution.
    For other solutions, divide both sides by x to get the quadratic
    (x+6)(x-4) = 24
    x^2 +2x -24 = 24
    x^2 +2x -48 = 0
    (x+8)(x-6) = 0
    x = -8 or 6

    Your answer is correct but you got there the hard way.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. algebra

    24x^4-12x^3+48x^2/-4x 24x^4-12x^3+12(-1) 24x^4-12x^3+(-12x) 2x^4-12x^3-12x check this problem for me please
  2. algebra

    -12X^6+24x^5-18x^2/-6x^2=2x^4+24x^3-3x could some one check this for me please
  3. Maths

    is this correct... (3x^2+4x-3)^2-(3x^2-x+2)^2 then is it this (9x^4+24x^3-2x^2-24x+9)-(9x^4-6x^3+13x^2-4x+4) or this 9x^4+24x^3-2x^2-24x+9-9x^4-6x^3+13x^2-4x+4 should it have brakets or not that's my only problem thanks
  4. math help

    5) Consider the equations: f(X)= -6x-1 and g(x)=4x^2 Select the solution for (f+g)(x). a) -6x -1 + 4x^2 b) -24x^3 - 4x^2 c) -24x^2 - 1 d) -6x - 1- 24x^2
  5. math help please

    12. (-8x) x (3x^2) -5x^3 -24x^2 -24x^3 -5x^2 13. (-11z)^0 z 1 -11 1 14. 14^-4 1/14^4 -56 1/14 1/14^-4 My answer: 12. -24x^3 13. -1 14. 1/14
  6. alg2 check?

    solve 3(8x-2)=46-2(12x+1) 24x-6=46-24x+2 24x-6=48-24x 48x-6=48 48x=42 x=42/48 or 7/8 what where the two mistakes made in the problem?
  7. Math

    consider the equations:f(x)=-6x-1 and g(x)=4x^2 Select the solution for (f+g)(x) A) -6x-1+4x^2 B) -24x^3 - 4X^2 C) -24x^2 - 1 D) -6X -1 - 24X^2 I think the answer is A. Please help
  8. MATH

    f(x)= -6x-1 and g(x)=4x^2 select the soultion for (f+g)(x) stuck not sure which answerer is correct -24x^2-1 or -24x^3-4x^2
  9. Math

    (2x-1)(3x-7)(4x+3) =6x^2-14x-33x+7 =(6x^2-19x+7)(4x+3) =24x^3+18x^2-126x+28x+21 =24x^3+18x^2-88x+21 <-- my answer but the correct answer is 24x^3-50x^2-23x+21 please correct me?
  10. algebra

    Please correct,if necessary, and simplify using long division: (-72-4x^2+8x^3-36x) devided by (x-3). My solution: 8x^2+20x+24 ------------------- 8x^3-4x^2-36x-72 8x^3-24x^2 ------------------ 20x^2-36x-72 20x^2-60x ----------------------- …

More Similar Questions